KAUM REMNANT, SIAPAKAH MEREKA? SUATU KAJIAN BIBLIKA TERHADAP TEKS YESAYA 10:20-23 - Kristiawan, Ragil (Shift Key : Jurnal Teologi dan Pelayanan, 2018)
This research seeks to find a definite identity regarding the Remnants recorded in Isaiah 10: 20-23. Various theories have been conveyed by Old Testament scholars about who the Remnants were. Some scholars conclude that the Remnants are only limited to the remnants of Assyria. Some consider that the Remnant refers to those who have returned from the Babylonian exile. In fact, some scholars consider that this also refers to future eschatological times. Through biblical studies that have been carried out with the right methodology, this research has produced a conclusion. These Prophecies of the Rest in Isaiah 10: 20-23 have multiple fulfillments. Fulfillment in its immediate context, the remnant refers to the remnants of Israel who escaped the savagery of Assyria and they later joined the Southern Kingdom. While the fulfillment in the distant context, these remnants point to a later eschatological period where God will truly gather Israel again as a nation. The distinctive feature possessed by the rest of Israel is the absolute loyalty to God (New Testament concept: Jesus Christ) and in the future there will be a fair government from God himself. From this conclusion there are also theologies and practical implications regarding the church today